The epidemiology of childhood blindness and severe visual impairment in Indonesia. Issue 11 (6th February 2018) - Muhit, Mohammad; Karim, Tasneem; Islam, Johurul; Hardianto, Denny; Muhiddin, Habibah Setyawati; Purwanta, Setia A; Suhardjo, Suhardjo; Widyandana, Doni; Khandaker, Gulam
Abstract : Background: The magnitude of blindness among children in Indonesia is unknown. In this study, we aimed to define the magnitude and aetiology of childhood blindness in two parts of Indonesia. Method: Children aged 0–15 years, identified through key informant method and from special schools and community-based rehabilitation programme in Sumba and Yogyakarta, were assessed following WHO protocol and definitions for ophthalmological assessment and classification of visual impairment and blindness among children. Results: Out of 195 children assessed, 113 had blindness/severe visual impairment (BL/SVI), 48 had visual impairment (VI) and 34 had no VI. 43.4% children with BL/SVI were female. The main anatomical site of BL/SVI was lens (n=35, 31.0%), followed by retina (n=13, 11.5%) and cornea (n=9, 8.0%). Among the known aetiologies, childhood factors predominated (n=14, 12.4%), followed by hereditary diseases (n=12, 10.6%) where parental consanguinity was found among 33.3% (n=4) of them. Overall, 77.8% (n=88) had avoidable causes of BL/SVI: 69.0% (n=78) treatable and 8.8% (n=10) preventable causes. The estimated prevalence of BL/SVI was 0.25 (95% CI 0.19 to 0.32) and 0.23 (95% CI 0.18 to 0.29) per 1000 children in Sumba and Yogyakarta, respectively. The estimated prevalence of cataract was 0.07 per 1000 children (95% CI 0.04 to 0.12) in Sumba and 0.05 per 1000 children (95% CI 0.03 to 0.09) in Yogyakarta. Based on our conservative estimates, there are 17 241 children with BL/SVI in Indonesia; 4270 are blind due to cataract. Conclusion: The magnitude of childhood BL/SVI in Sumba and Yogyakarta is high. Our study suggests that a large proportion of childhood BL/SVI in Indonesia is avoidable.